Intervención desde la teoría cognitiva para enfrentar la conducta bullying en los estudiantes del primer año de bachillerato del Colegio Remigio Geo Gómez Guerrero de la ciudad de Huaquillas, de la Provincia de El Oro, en el periodo lectivo 2014-2015. - Gómez Atto, Erika Alexandra (2015)
From a psychological aspect clinical research was conducted at the College Remigio Gomez Guerrero Geo City Huaquillas that allows us to know the current situation in which the institution is located regarding bullying behaviors between students and the institution if there a method of intervention to address this problem. The bullying behaviors are prevalent in educational institutions because they generally affect both physical and mental well-being of students deteriorating academic performance. Qualitative-quantitative methods was used from a rational-deductive epistemological approach to the operationalization of the research, conducted surveys applied to students and teachers of the institution. They were processed and analyzed the data from the survey of students and teachers were compared, allowing know the reality of the research object, which is used to design the proposed intervention. Similarly formulate conclusions and recommendations. The proposal is directed from a clinical approach, focusing on providing the best professional intervention strategies to address bullying behavior in the institution, an action that resonate with students, teachers, family and society. From a psychological aspect clinical research was conducted at the College Remigio Gomez Guerrero Geo City Huaquillas that allows us to know the current situation in which the institution is located regarding bullying behaviors between students and the institution if there a method of intervention to address this problem. The bullying behaviors are prevalent in educational institutions because they generally affect both physical and mental well-being of students deteriorating academic performance. Qualitative-quantitative methods was used from a rational-deductive epistemological approach to the operationalization of the research, conducted 15 surveys applied to students and teachers of the institution. They were processed and analyzed the data from the survey of students and teachers were compared, allowing know the reality of the research object, which is used to design the proposed intervention. Similarly formulate conclusions and recommendations. The proposal is directed from a clinical approach, focusing on providing the best professional intervention strategies to address bullying behavior in the institution, an action that resonate with students, teachers, family and society.